Glorification of The Roaring Twenties in Woody Allen’s Midnight in Paris (2011): a Biographical Criticism - Devika Tiara Raharjo; M. Thoyibi (Ruang Kata, 2026)
This study aims to analyse the glorification of the Roaring Twenties in Woody Allen’s Midnight in Paris through a biographical criticism approach. This study employs a qualitative descriptive approach using biographical criticism to analyse the glorification of the Roaring Twenties in Woody Allen’s Midnight in Paris (2011). The data consist of dialogues, visual scenes, and audio elements taken from the film, supported by secondary sources such as scholarly articles and director interviews. The analysis is conducted through hermeneutic interpretation to examine how narrative, visual, and sound elements reflect Allen’s personal worldview and artistic longing. The findings reveal that Midnight in Paris (2011) strongly glorifies the Roaring Twenties through nostalgic figures, events, products, characterisation, style, and setting. The film represents the 1920s as a cultural and artistic golden age, portraying writers and artists as idealised cultural icons while emphasising creativity, elegance, and emotional fulfilment. This romanticised depiction contrasts sharply with the cynical, materialistic modern world, illustrating how nostalgia functions as an emotional response to contemporary dissatisfaction and shapes viewers’ perceptions of the past.